2017
DOI: 10.1002/pen.24499
|View full text |Cite
|
Sign up to set email alerts
|

Inverse emulsion free‐radical polymerization of acrylamide terpolymer for enhanced oil recovery application in harsh reservoir conditions

Abstract: A free-radical inverse emulsion polymerization formulation has been developed for preparation of acrylamide (AAm)/sodium 2-acrylamido-2-methylpropanesulfonate (AMPSNa)/N-vinylpyrrolidone (VP) terpolymers. An aqueous solution of a blend of monomers is emulsified in ndecane using Tween 85 (Tw85). Ammonium persulfate (APS) and dicumyl peroxide (DCP) were used as initiators for water and oil phases, respectively. The reactions were catalyzed by temperature and by a redox pair; the former is achieved at 608C and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…After the emulsification process, the emulsion type was determined by the phase dilution method . Moreover, the conductivity of freshly prepared inverse emulsions was measured using a FE30 conductivity meter (Mettler Toledo, Switzerland) with a quartz conductivity probe.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the emulsification process, the emulsion type was determined by the phase dilution method . Moreover, the conductivity of freshly prepared inverse emulsions was measured using a FE30 conductivity meter (Mettler Toledo, Switzerland) with a quartz conductivity probe.…”
Section: Methodsmentioning
confidence: 99%
“…Inverse emulsion polymerization (IEP) is a candidate method to produce high‐molecular‐weight polymers with low bulk viscosity . Candau group prepared hydrophobically associating polymers using AM, sodium acrylate (NaAA) and a series of amphiphilic comonomers by IEP, and the M w of the final products can reach 5 × 10 6 –6 × 10 6 g·mol −1 .…”
Section: Introductionmentioning
confidence: 99%
“…García‐Uriostegui et al introduced the preparation of terpolymer (AM/ATBS/NVP) by free radical inverse emulsion polymerization. The terpolymer has good stability and its salt resistance was 28,443 mg/L and temperature resistance was 92°C 26 . Hsieh et al found that the terpolymer (AM/ATBS/NVP) has excellent thermal stability and can maintain good thermal stability in seawater at 149°C 27 .…”
Section: Introductionmentioning
confidence: 99%
“…In this work, β-CD was used as the main material to synthesize a highly efficient hydrophobic composite polymer flocculant, and throughout the course of the study the amount of harmful reagents used was strictly controlled to protect the environment. Hydrophobic β-CD was introduced into the traditional polyacrylamide flocculating materials, simultaneously based on redox-free radical solution reaction, copolymerized with dimethyl diallylammonium chloride monomer to prepare cationic polyacrylamide-cyclodextrin composite polymer flocculation material to improve flocculation performance [18][19][20][21], reduce the accumulation of dyes in the environment and achieve win-win results for economic and environmental benefits.…”
Section: Introductionmentioning
confidence: 99%